The influence of oxidative debris on the fragmentation and laser desorption/ionization process of graphene oxide derivatives - Hong, Yu Lim; Lee, Jieon; Ku, Bon-Cheol; Kang, Kyungtae; Lee, Seunghyun; Ryu, Seongwoo; Kim, Young-Kwan (ROYAL SOC CHEMISTRY, 2018)
The effect of oxidative debris (OD) on the fragmentation behavior and the laser desorption/ionization (LDI) process of graphene oxide (GO) derivatives was systematically investigated to explore the potential of LDI time-of-flight mass spectrometry (LDI-TOF-MS) as a characterization tool for their chemical structure and photochemical properties. Based on the results, we found that the fragmentation patterns and the LDI properties of the GO derivatives were highly affected by the OD adsorbed on their surface. Our findings suggest that LDI-TOF-MS can be a useful analytical tool for determining the chemical structure and photochemical properties of GO derivatives.
Keywords: MASS-SPECTROMETRY; SMALL MOLECULES; MULTILAYER FILMS; NANOSHEETS; MODEL